A TGF-βR/IL-2R immunomodulatory fusion protein transforms immunosuppression into T cell activation to enhance adoptive T cell therapy - Yapeng Su; Ashley Thelen; Lena V. Wirth; Cody M. Jenkins; Sam R. Mak; Daniel G. Chen; Raphael Gottardo; Philip D. Greenberg (Proceedings of the National Academy of Sciences, 2025)
Adoptive T cell therapies have shown limited efficacy against solid tumors due in part to immunosuppressive cues such as from TGF-β and insufficient survival/proliferative signals within the tumor microenvironment (TME). We engineered chimeric immunomodulatory fusion proteins (IFPs) that convert immunosuppressive TGF-β signals into proliferative/survival Interleukin 2 (IL-2) signals in T cells. Chimeric TGF-βR/IL-2R IFPs were constructed by fusing extracellular domains of the TGF-β receptor chains with intracellular domains of IL-2Rβ and IL-2Rγ to enable TGF-β binding to trigger STAT5 phosphorylation and activate the downstream IL-2 pathway. In human primary CD8 + T cells, select IFP designs robustly induced p-STAT5 upon exposure to TGF-β1, and simultaneously reduced canonical SMAD2/3 signaling. IFP-expressing T cells proliferated and displayed enhanced viability in response to TGF-β1, effectively leveraging TGF-β-rich conditions to outcompete nontransduced cells. Transcriptomic analyses revealed that IFP signaling promoted T cell activation and allowed maintenance of stemness during culture with TGF-β. Functionally, coexpressing IFPs with a mesothelin-specific T cell receptor improved tumor killing and promoted T cell expansion in the presence of TGF-β1, highlighting both neutralization of TGF-β–mediated suppression and enhanced proliferation. TGF-βR/IL-2R IFPs appear promising for reprogramming the signals T cells receive in the TME and improving efficacy of adoptive T cell therapy in solid tumors.